2021
DOI: 10.1051/e3sconf/202131602045
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Red Rice Farming in Gunung Kidul Regency, Yogyakarta

Abstract: Red rice is germplasm in Gunung Kidul Regency, whose territory is north, central, and south. This study aimed to analyze the factors that influence the production of red rice farming in Gunung Kidul Regency, analyze the level of technical efficiency, and the factors that influence the technical inefficiency of red rice farming in Gunung Kidul Regency. This research was conducted in Gunung Kidul Regency, which was determined purposively, in sampling 200 respondents. Data were analyzed using the Cobb-Douglas Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…Based on this data means that farmers still have a 11 -15% chance of increasing cassava production. Farmers were categorized as efficient if they have an efficiency index value of more than 0.7 (Rahayu & Hanifah, 2021). This showed that the average cassava farmer in Socah Village has been quite efficient, because from the average value in table 2 the value is 0.87.…”
Section: Technical Efficiency Of Cassava Farmingmentioning
confidence: 99%
“…Based on this data means that farmers still have a 11 -15% chance of increasing cassava production. Farmers were categorized as efficient if they have an efficiency index value of more than 0.7 (Rahayu & Hanifah, 2021). This showed that the average cassava farmer in Socah Village has been quite efficient, because from the average value in table 2 the value is 0.87.…”
Section: Technical Efficiency Of Cassava Farmingmentioning
confidence: 99%